Fermented camel milk enriched with plant sterols improves lipid profile and atherogenic index in rats fed high -fat and -cholesterol diets. Issue 10 (October 2022) - Althwab, Sami A.; Alamro, Samar A.; Al Abdulmonem, Waleed; Allemailem, Khaled S.; Alarifi, Saud A.; Hamad, Essam M.
Abstract: The current study was designed to explore the effect of fermented camel milk, plant sterols and their combination on the blood levels of sd-LDL and atherogenicity in rats fed on high-fat-cholesterol diets (HFC). Forty male Wistar rats were distributed into five groups: Normal control (NC), Positive control (PC, HFC), plant sterol (PS, HFC containing 1% (w/w) β-sitosterol:Stigmasterols; 9:1), FM (HFC containing 4% (w/w) lyophilized fermented camel milk), and PSFM (HFC containing 1% (w/w) plant sterols +4% (w/w) lyophilized fermented camel milk). Antioxidant activity showed that β-sitosterol had the highest radical scavenging activity, followed by fermented camel milk and stigmasterol (p < 0.05). Feeding rats on HFC for 8 weeks resulted in a significant (p < 0.05) increase in blood lipids of PC group compared with NC group. Administration of PS, FM, and PSFM resulted in a significant reduction in atherogenic index (50, 24.5, and 41.5 %, p < 0.05), and sd-LDL levels (73, 45, and 59%, p < 0.05), respectively. Only the FM group showed a significant reduction in triglycerides levels of rats. Administration of PS, FM and PSFM decreased serum MDA levels significantly by 58.7, 45.4, and 69% (p < 0.05), and increased total antioxidant capacity by 35.9, 84.8, and 38.3% (p < 0.05), respectively. This is the first report to the best of our knowledge that shows fermented camel milk enriched with plant sterol could reduce atherogenesis and cardiovascular diseases activity via inhibition of the status of small dense LDL and oxidative stress. Abstract : Cardiovascular disease; Small dense LDL; High fat cholesterol diet; Plant sterols; Fermented camel milk; Oxidative stress.